Nanostructure of clustered DNA damage in leukocytes after in-solution irradiation with the alpha emitter Ra-223 - Scherthan, Harry; Chojowski, Robert; Hausmann, Michael (Cancers, 2019)
Background: Cancer patients are increasingly treated with alpha-particle-emitting radiopharmaceuticals. At the subcellular level, alpha particles induce densely spaced ionizations and molecular damage. Induction of DNA lesions, especially clustered DNA double-strand breaks (DSBs), threatens a cell’s survival. Currently, it is under debate to what extent the spatial topology of the damaged chromatin regions and the repair protein arrangements are contributing. Methods: Super-resolution light microscopy (SMLM) in combination with cluster analysis of single molecule signal-point density regions of DSB repair markers was applied to investigate the nano-structure of DNA damage foci tracks of Ra-223 in-solution irradiated leukocytes. Results: Alpha-damaged chromatin tracks were efficiently outlined by γ-H2AX that formed large (super) foci composed of numerous 60–80 nm-sized nano-foci. Alpha damage tracks contained 60–70% of all γ-H2AX point signals in a nucleus, while less than 30% of 53BP1, MRE11 or p-ATM signals were located inside γ-H2AX damage tracks. MRE11 and p-ATM protein fluorescent tags formed focal nano-clusters of about 20 nm peak size. There were, on average, 12 (±9) MRE11 nanoclusters in a typical γ-H2AX-marked alpha track, suggesting a minimal number of MRE11-processed DSBs per track. Our SMLM data suggest regularly arranged nano-structures during DNA repair in the damaged chromatin domain.